2017
DOI: 10.1063/1.4996133
|View full text |Cite
|
Sign up to set email alerts
|

Ce in the +4 oxidation state: Anion photoelectron spectroscopy and photodissociation of small CexOyHz− molecules

Abstract: The anion photoelectron (PE) spectra of a range of small mono-cerium molecular species, along with the CeO and CeO stoichiometric clusters, are presented and analyzed with the support of density functional theory calculations. A common attribute of all of the neutral species is that the Ce centers in both the molecules and clusters are in the +4 oxidation state. In bulk ceria (CeO), an unoccupied, narrow 4f band lies between the conventional valence (predominantly O 2p) and conduction (Ce 5d) bands. Within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 52 publications
4
20
0
Order By: Relevance
“…In recent studies, Chick Jarrold and coworkers presented the structure and bonding of various lanthanide oxides and hydroxides, some of which involve multiple lanthanide-oxygen bonds. 1,14,[76][77] In agreement with our results, their experimental photoelectron spectroscopic studies and supporting DFT calculations have shown that Ln(I) complexes (e.g.…”
Section: Resultssupporting
confidence: 92%
“…In recent studies, Chick Jarrold and coworkers presented the structure and bonding of various lanthanide oxides and hydroxides, some of which involve multiple lanthanide-oxygen bonds. 1,14,[76][77] In agreement with our results, their experimental photoelectron spectroscopic studies and supporting DFT calculations have shown that Ln(I) complexes (e.g.…”
Section: Resultssupporting
confidence: 92%
“…In recent studies, Chick Jarrold and coworkers presented the structure and bonding of various lanthanide oxides and hydroxides, some of which involve multiple lanthanide-oxygen bonds. 1,14,[76][77] In agreement with our results, their experimental photoelectron spectroscopic studies and supporting DFT calculations have shown that Ln(I) complexes (e.g. EuOH 1 ) favor a linear geometry, while lanthanide complexes with a higher coordination number (two or more hydroxide ligands coordinated to the lanthanide center) and corresponding higher lanthanide oxidation state (+2, +3, etc.)…”
Section: Resultssupporting
confidence: 91%
“…yield bent Ln-O-H angles between 140 o and 160 o . 14,77 Table S2. Occupations of 4f, 5d, and 6s based non-bonding molecular orbitals of lanthanide hydroxides as described in the paper.…”
Section: Resultsmentioning
confidence: 99%